Characteristics of Methane Micro-seepage in Low-rank Coal Pores of Ordos Basin - ZHANG Fei, ZHANG Pan (Meikuang Anquan, 2020)
In order to obtain the true micro-pore structure of the coal seams and reveal the micro-seepage characteristics of methane in the pore system, X-ray μCT scanning experiment was carried out for low-rank coal in Ordos Basin. The micro-pore space structure was reconstructed and characterized. The connected pores were reversely optimized and numerically modeled. Numerical simulation of methane micro-seepage was used to explore its characteristics. The results show that: the micro-pore structure of coal has strong heterogeneity, and its shape is close to spherical. There is an exponential relationship between the pore shape factor and the equivalent diameter. There are large micro-fissures in Yangchangwan Mine brown coal, while the number of micro-fissures in Xiegou Mine gas coal is small, and there are multiple pore groups in the local area. Seepage pore size is not the only factor that determines the seepage performance of methane, but more depends on its connectivity. The non-uniformity of methane pressure in the same pore reflects the selective direction of seepage flow.